Energy-smart buildings : design, construction and monitoring of buildings for improved energy efficiency - Lamb, Jacob J.; Pollet, Bruno G. (IOP ebooks. 2020 collection., 2020)
This volume intends to provide a brief research source for building technology and regulations in terms of energy efficiency, discussing fundamental aspects as well as cutting-edge trends for new buildings and retrofitting the current building stock. Sources of renewable and sustainable energy production and storage are additionally reviewed, with case studies of such systems on buildings in a cold climate. This volume also provides industry professionals, researchers and students with the most updated review on modern building ideas, and renewable energy technologies that can be coupled with them. Part of IOP Series in Renewable and Sustainable Power.